PERANCANGAN SISTEM INFORMASI BOOKING WEDDING PLANNER BERBASIS WEBSITE PADA HARUM SENJA DECORATION - Selvira, Annisha; Bangun, Elsi Titasari Br; Maulana, Galih Suryo; Karuniawati, Sri (JURNAL ILMIAH INFORMATIKA, 2025)
Harum Senja Decoration, a wedding planning service provider, previously relied on social media platforms like Instagram for marketing and bookings. This process was done manually, resulting in the risk of confirmation delays and recording errors. This study aims to design a website-based booking information system to improve the efficiency, accuracy, and ease of booking services for prospective brides and grooms. The development method used is the Prototype model, which allows for gradual system improvements based on user feedback. The development stages include needs analysis, system design (use case diagrams, activity diagrams, sequence diagrams, class diagrams, and flowcharts), and implementation with HTML, CSS, JavaScript, and XAMPP for the database. System testing used the Black-Box Testing method, ensuring all functions run according to specifications. The result of this study is a web-based information system that includes login features, package booking, payment, data management by admins, and automatic notifications. With this system, the booking process is more structured, faster, and can be monitored in real-time by users and managers. This system is expected to provide solutions to previous operational problems and improve the quality of digital wedding planning services.